Who Will Be the Next President? A Guide to the U.S. Presidential Election System - Belenky, Alexander S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book is open access under a CC BY 4.0 license.
1 The Initial Design of the Electoral College: Basic Ideas,Logical Mistakes, and Overlooked Problems -- 2 The Electoral College Today -- 3 Curbing Contingent Elections -- 4 Inconvenient Facts About the Electoral College -- 5 The Electoral College and Campaign Strategies -- 6 The National Popular Vote Plan: A Brilliant Idea or a Dead-on-Arrival Delusion? -- 7 Equalizing the Will of the States and the Will of the Nation -- 8. Conclusion: Fundamental Merits, Embedded Deficiencies, and Some Urgent Problems of the U.S. Presidential Election System.
Keywords: Private international law; Conflict of laws; International law; Comparative law; America$1 (BPolitics and government.s; Law$1 (BPhilosophy.s; Law$1 (BHistory.s; Elections; Mathematics; Social sciences; Private International Law, International and Foreign Law, Comparative Law; American Politics; Theories of Law, Philosophy of Law, Legal History; Electoral Politics; Mathematics in the Humanities and Social Sciences